Lời giải:
ĐK: $m\in (-1;+\infty)$
$y'=\frac{2m(x+2)-x^2}{(m-x)^2}
Để hàm số nghịch biến trên $(-\infty;-1]$ thì $2m(x+2)-x^2\leq 0, \forall x\in (-\infty;-1](*)$
+) $m=-2$ thì luôn đúng
+) $m\neq -2$ thì \((*)\Leftrightarrow \left\{\begin{matrix} m\geq \frac{x^2}{2(x+2)}, \forall x< -2\\ m\leq \frac{x^2}{2(x+2)}, \forall -1\geq x> -2\end{matrix}\right.\)
\(\Leftrightarrow \left\{\begin{matrix} m\geq-4\\ m\leq \frac{1}{2}\end{matrix}\right.\). Kết hợp với ĐKXĐ của $m$ suy ra $m\in (-1; \frac{1}{2}]$
$\Rightarrow 2b+a=1+(-1)=0$
Đáp án B.